Extensional Flow of Water and a Semi-Dilute Aqueous Solution of Polyethylene Oxide through Microfabricated Hyperbolic Contractions - Mónica S. Neves Oliveira (2006)
The flow of a Newtonian fluid and a viscoelastic semi-dilute aqueous solution of polyethylene oxide (PEO) through microfabricated hyperbolic contractions was studied experimentally. A set of planar converging geometries, with total Hencky strains ranging from 1 to 3.7, were designed to produce an extensional flow field within the contraction. The flow in the contraction region was experimentally investigated by means of streak photography and micro particle image velocimetry (µPIV). Using this laser based technique, we were able to characterize quantitatively the velocity field at a given plane in the hyperbolic contraction. The pressure drop across the converging geometry was also measured and non-linear effects, attributable to viscoelasticity, were observed for the PEO solution. The Newtonian results compared favorably with those predicted numerically using a finite-volume method.